Multisite Injection of Corticosteroids is more Efficient than a Single Glenohumeral Injection in Treating Acute Frozen Shoulder - Abdul Munaf Saud, Naveed Gul, Abdul Rauf Tippu, Mazhar Mahmood, Mohammad Abid, Irtiza Ahmed Bhutta, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To compare the effectiveness of a single glenohumeral injection versus multisite injection of corticosteroids in treating acute frozen shoulder. Study design: Randomized controlled trial Setting and duration: Department of Orthopedic Surgery Civil Hospital Bahawalpur from January 2022 to December 2022. Material and methods: Total 74 patients with acute frozen shoulder having onset of symptoms within the last 12 months were included. This study compared the functional ratings, Mobility, and pain alleviation of patients with primary Frozen Shoulder (FS) after different period of follow up in our OPD. In multisite group, triamcinolone acetonide, bupivacaine and saline were injected into four different sites. In the single glenohumeral injection group, only the glenohumeral joint was injected. Both groups received physiotherapy after injection, including soft tissue therapy, joint mobilization and a home exercise program. The outcome measures were assessed through Range of motion, function and pain scores at a follow up of every three months, six months and then after one year. Results: According to the study, the patients receiving injections at multisite outperformed those receiving single-injection on the visual analogue scale (VAS) at all follow-up intervals (P = 0.01). Moreover, compared to the single-injection group, the multisite-injection group had substantially superior active and passive ROM restoration (P 0.05) and higher functional scores (P 0.05). Practical Implication: It suggests multisite injections as a treatment for frozen shoulder, in contrast to prior studies. Positive characteristics of the study include the use of a blinded clinical examination and the presence of a sufficient number of participants Conclusion: In conclusion, multisite injection of corticosteroids has more potency than a single injection in reducing pain in patients with acute frozen shoulder. Clinicians may consider multisite injection as a preferred method of treatment for primary frozen shoulder, especially in patients with severe pain. Keywords: multisite injection, frozen shoulder, glenohumeral injection, pain, stiffness